Over-expression of a fungal NADP(H)-dependent glutamate dehydrogenase PcGDH improves nitrogen assimilation and growth quality in rice - Zhou, Yanbiao; Liu, Hong; Zhou, Xiangcheng; Yan, Yuanzhu; Du, Changqing; Li, Yixing; Liu, Derong; Zhang, Caisheng; Deng, Xiaolong; Tang, Dongying; Zhao, Xiaoying; Zhu, Yonghua; et al. (Molecular breeding, 2014)
Glutamate dehydrogenase (GDH) tends to have a lower affinity for ammonium than glutamine synthetase (GS) in higher plants. Consequently, nitrogen is mostly assimilated as ammonium by the GS/glutamate synthase pathway which requires 2-oxoglutarate (2-OG) as carbon skeletons. In contrast, the NADP(H)-dependent GDH in fungi has a higher affinity for ammonium than that in higher plants and plays a more significant part in ammonium assimilation. We isolated an NADP(H)-GDH gene (PcGDH) from the fungus Pleurotus cystidiosus and heterologously expressed it in rice (Oryza sativa L.). Alterations in nitrogen assimilation, growth, metabolism, and grain yield were observed in the transgenic plants. An investigation of the kinetic properties of the purified recombinant protein demonstrated that the amination activity (7.05 ± 0.78 μmoL min⁻¹ mg soluble protein⁻¹) of PcGDH was higher than the deamination activity (3.36 ± 0.42 μmoL min⁻¹ mg soluble protein⁻¹) and that the K ₘ value for ammonium (K ₘ = 3.73 ± 0.23 mM) was lower than that for the glutamate (K ₘ = 15.97 ± 0.31 mM), indicating that the PcGDH tends to interconvert 2-OG and glutamate. Examination of the activity of NADP(H)-GDH in control and transgenic lines demonstrated that NADP(H)-GDH activity in the transgenic lines was markedly higher than that in the control lines; in particular, the amination activity was significantly higher than the deamination activity in shoots of the transgenic lines. The results of the hydroponics experiment revealed that shoot and root length, fresh weight, chlorophyll content, nitrogen content, and amino acid levels (glutamate, glutamine, and total amino acids) were elevated in transgenic lines in comparison with those of the control line under different nitrogen conditions at seedling stage. The 1,000-grain weight and the panicle number in transgenic lines were considerably augmented in the field condition, yet the filled grain rate dropped slightly and there was no apparent change in the grain yield. The levels of glutelin and prolamine in the transgenic seeds were considerably higher than those in control seeds. In conclusion, these results demonstrate that heterologous expression of P. cystidiosus GDH (PcGDH) could improve nitrogen assimilation and growth in rice.